Nonviral gene delivery to T cells with Lipofectamine LTX. Issue 4 (2nd February 2021) - Harris, Emily; Zimmerman, Devon; Warga, Eric; Bamezai, Anil; Elmer, Jacob
Abstract: Retroviral gene delivery is widely used in T cell therapies for hematological cancers. However, viral vectors are expensive to manufacture, integrate genes in semirandom patterns, and their transduction efficiency varies between patients. In this study, several nonviral gene delivery vehicles, promoters, and additional variables were compared to optimize nonviral transgene delivery and expression in both Jurkat and primary T cells. Transfection of Jurkat cells was maximized to a high efficiency (63.0% ± 10.9% EGFP + cells) by transfecting cells with Lipofectamine LTX in X‐VIVO 15 media. However, the same method yielded a much lower transfection efficiency in primary T cells (8.1% ± 0.8% EGFP + ). Subsequent confocal microscopy revealed that a majority of the lipoplexes did not enter the primary T cells, which might be due to relatively low expression levels of heparan sulfate proteoglycans detected via messenger RNA‐sequencing. Pyrin and HIN (PYHIN) DNA sensors (e.g., AIM2 and IFI16) that can induce apoptosis or repress transcription after binding cytoplasmic DNA were also detected at high levels in primary T cells. Therefore, transfection of primary T cells appears to be limited at the level of cellular uptake or DNA sensing in the cytoplasm. Both of these factors should be considered in the development of future viral and nonviral T cell gene delivery methods. Abstract : Harris et al. show that Lipofectamine efficiently transfects adherent PC‐3 cells, but a lack of heparan sulfate proteoglycan expression and other factors limit lipoplex uptake in primary T cells. This image is an artistic representation of confocal microscopy observations (see Figure 6 in the manuscript for actual images) that show fluorescent plasmid DNA (green) is readily taken up in PC‐3 cells (left; stained with Hoechst 33342 and CellBrite Red), but endocytosis is limited in primary T cells (right).